Comparison of Kinesio Taping, Trigger Point Injection, and Neural Therapy in the Treatment of Acute Myofascial Pain Syndrome: A Randomized Controlled Study - Ay, Saime; Tur, Birkan Sonel; Karakaş, Merve; Gökmen, Derya; ALTINBİLEK, TURGAY; Evcik, Deniz (Kare Publishing, 2023)
Objectives: Myofascial pain syndrome (MPS) is a regional painful soft-tissue disorder, characterized by trigger points (TrPs) and taut bands in the muscles. In this study, we aimed to compare the effectiveness of kinesio taping (KT), TrPs injection, and neural therapy (NT) on pain and disability in acute MPS.Methods: 104 patients with MPS in the cervical region were allocated into three groups. Group 1 (n=35) were treated with KT, Group 2 (n=35) received local anesthetic (LA) (lidocaine of 0.5%) TrPs injection, and Group 3 (n=34) received NT with the same LA solution. Patients were assessed by means of pain, pressure pain threshold (PPT), and disability. Pain severity was measured by Visual Analog Scale. The neck pain disability scale was used for assessing disability. PPT was measured by using an algometer. Measurements were taken before and after treatment of 3(rd) and 7(th) days.Results: There were improvements on pain and disability in all groups at the end of treatments at 3(rd) day and during follow-up period (p<0.001) and no differences were found between the groups. There was significant difference in PPT values in TrPs injection and NT groups in comparisons between all time periods, however, the change, depending on time in the KT group, was not statistically significant.Conclusion: The results of this study show that all these three treatment methods found to be effective on pain relief and disability in acute MPS. In terms of PPT, injection treatments seem to be superior than KT.
Keywords: Acute Pain; Disability; Injection; Kinesio Taping; Myofascial Pain; Neck Pain; Neural Therapy; Trigger Point